Variasi Morfologi Holdfast Lernaea yang Menyerang Ikan Gurami di Jawa Timur [Morphological Variation Of Lernaea Holdfast Infest Gouramy In East Java] - Kismiyati Kismiyati; Putri Desi Wulan Sari (Jurnal Ilmiah Perikanan dan Kelautan, 2014)
Abstract Lernaeosis is one of the parasitic diseases in freshwater fish caused by Lernaea cyprinacea. These parasites infest many freshwater fish. Identification of parasites carried by observing the morphology of holdfast as an attachment organ. This study aims to make observations on the variation of morphology of Lernaea holdfast's in East Java and the identification of Lernaea infest gouramy in East Java.